Meteorological aspects of arid and semi-arid regions of India with special reference to Thar desert - CHOWDHURY, A.; BANERJEE, A. K.; GOKHALE, S. S. (MAUSAM, 1980)
In this review paper general climatological features of rainfall including rainy days maximum and minimum, temperatures, annual evaporation, droughts and floods, thunderstorms, hailstorms and duststorrns, and the water balance aspects, namely, water surplus and water deficit, over arid and semi-arid regions of the country have been discussed. A review has also been made of the studies on climatic fluctuations over this area. It has been observed that the climatic elements do not exhibit presence of any regular Pattern. It was therefore, concluded that there is no reason to believe that the Rajasthan desert is accentuating or spreading.